Comparison of Visitor Preferences and Satisfaction Between Old and New Markets in Semarang City - Enik Rahayu; Hendrajaya Hendrajaya; C. Susmono Widagdo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines visitor satisfaction and market preferences in traditional and modern markets in Semarang City, Indonesia, focusing on five key variables: product price, product quality, service quality, market facilities, and market atmosphere. The research addresses the declining competitiveness of traditional markets amid urban modernization and the rise of modern and digital retail systems. The goal is to identify dominant factors influencing consumer preferences and satisfaction in hybrid market competition. A quantitative method was used, involving a structured questionnaire distributed to market visitors. Data were analyzed using multiple linear regression to determine the impact of each variable on consumer satisfaction and market preferences. The results indicate that service quality is the most influential factor, followed by product quality and market facilities. While product price and market atmosphere also play roles, their effects are less significant. These findings suggest that consumer behavior is shaped not only by economic considerations, but also by the overall shopping experience and service interactions. The model used in this study has a high explanatory value (R² = 0.914), reflecting the strength of the predictive framework. This confirms that enhancing service and improving physical infrastructure are key to increasing the appeal of traditional markets. This research contributes to discussions on retail transformation and offers insights for local governments, market administrators, and vendors. It emphasizes the need to balance modernization efforts with improvements in traditional retail spaces. However, the study is limited to a specific region and does not explore digital market influences. Future research should broaden the geographic scope, incorporate online shopping behavior, and use longitudinal approaches to better inform policy and strategic development.